(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
History of recording of occasional units is presented in home linguistics that takes beginning from. The achievements of home individually-author’s neography are analyzed, in particular results of the lexicographic working of poetic neolexemes that considerably activated during the last decades. The basic lexicographic parameters of vocabulary entries in neographic revisions are defined. The problems of home neography are outlined, related to making of common principles of creation of dictionaries of new formations on the whole and separate authors in particular, with the outline of ways of identification of occasional words.